Deregulating the transfer of agricultural technology: lessons from Bangladesh, India, Turkey, and Zimbabwe - Gisselquist, David; Pray, Carl; Nash, John (2002)
Many transition and developing economies have reduced direct public involvement in the production and trade of seed and other agricultural inputs. This trend creates opportunities for farmers to realize improved access to inputs, including technology from international private research. Unfortunately, input regulations often derail these opportunities by blocking private entry and the introduction of private technology. This study looks at the experience in Bangladesh, India, Turkey, and Zimbabwe to see whether regulations make a difference in agriculture and input industries in developing economies. In all countries, companies and farmers responded to regulatory reforms by introducing and adopting more new technology and by expanding the production, trade, and use of inputs. The increased use of private technology has brought higher yields and incomes, allowing farmers and consumers to reach higher levels of welfare. These results challenge governments to open their regulatory systems to allow market entry and the introduction of private technology through seeds and other inputs. - Reproduced.
Keywords: Agriculture